Perfectionism and Fear of Missing Out Among Junior High School Students: The Mediating Role of Social Media Intensity - Umar Diharja; Joko Kuncoro (Psikostudia : Jurnal Psikologi, 2026)
The digital era triggers pressure for an idealized image and social comparison among adolescents, leading to the anxiety of missing out on rewarding moments, known as Fear of Missing Out (FOMO). Perfectionism exacerbates this condition. This study aims to examine the correlation between perfectionism and Fear of Missing Out (FOMO) among junior high school students who actively use social media. The study employed a quantitative correlational design involving 120 students (64 female, 56 male) from two junior high schools in Lubuk Linggau, selected through purposive sampling. Perfectionism was measured using the Multidimensional Perfectionism Scale (MPS) by Hewitt and Flett (1991), while FOMO was measured using the Fear of Missing Out Scale (FoMOs) by Przybylski et al. (2013). Data were analyzed using Pearson correlation and simple linear regression with IBM SPSS Statistics version 22. Results showed a strong positive correlation between perfectionism and FOMO (r = 0.704; p < 0.01). Among the three dimensions, SPP demonstrated the strongest correlation with FOMO (r = 0.699), followed by SOP (r = 0.468) and OOP (r = 0.514). Perfectionism accounted for 70.4% of FOMO variance (R² = 0.704; F = 115.638; p < 0.001). These findings suggest that maladaptive perfectionism, particularly perceived social pressure, is a key mechanism underlying FOMO among adolescents.Era digital memicu tekanan citra ideal dan perbandingan sosial pada remaja, yang memunculkan kecemasan tertinggal momen berharga atau Fear of Missing Out (FOMO). Perfeksionisme memperburuk kondisi ini. Penelitian ini bertujuan mengkaji hubungan antara perfeksionisme dan Fear of Missing Out (FOMO) pada siswa Sekolah Menengah Pertama (SMP) pengguna media sosial. Penelitian menggunakan pendekatan kuantitatif desain korelasional dengan melibatkan 120 siswa (64 perempuan, 56 laki-laki) dari dua SMP di Lubuk Linggau yang dipilih melalui teknik purposive sampling. Perfeksionisme diukur menggunakan Multidimensional Perfectionism Scale (MPS) dari Hewitt dan Flett (1991), sedangkan FOMO diukur menggunakan Fear of Missing Out Scale (FoMOs) dari Przybylski et al. (2013). Analisis data menggunakan korelasi Pearson dan regresi linear sederhana melalui IBM SPSS Statistics versi 22. Hasil penelitian menunjukkan korelasi positif yang kuat antara perfeksionisme dan FOMO (r = 0.704; p < 0.01). Di antara tiga dimensi, SPP menunjukkan korelasi paling kuat dengan FOMO (r = 0.699), diikuti SOP (r = 0.514) dan OOP (r = 0.468). Perfeksionisme mampu menjelaskan 70,4% variansi FOMO (R² = 0.704; F = 115.638; p < 0.001). Temuan ini mengimplikasikan bahwa perfeksionisme maladaptif, khususnya tekanan sosial yang dipersepsi, merupakan mekanisme utama yang mendasari FOMO pada remaja.